Overweight and obesity and its determinants in primary school students: a population-based study from Iran - Behnam Honarvar; Leila Erfannia; Fatemeh Rafiee; Elham Zahmatkeshan; Faranak Balaghi Inaloo; Najmeh Hamzavizarghani; Ali Davoodi; Fatemeh Yarmahmoodi; Naeimehossadat Asmarian; Parisa Keshani; Azam Goodarzi; Yasman Movahednejad; et al. (Scientific Reports)
Abstract The increasing rate of obesity in children and adolescents is alarming, worldwide. This population-based study, conducted in 2024 in Fars Province, Iran, aimed to assess the prevalence of overweight and obesity among primary school students. In the 1st phase, the weight and height of 9853 students who were selected by multi-stage cluster random sampling from 36 districts were measured standardly. Then using World Health Organization AnthroPlus software, body mass index-for-age z-score (BAZ) of each subject was calculated and exported to the SPSS. Analysis showed the overall prevalence of overweight/obesity was 26.5% (n = 2616), including 14.7% (n = 1450) as overweight, 9.4% (n = 927) as obese, and 2.4% (n = 239) as severe obese. Logistic regression showed older students, who with normal height, and who lived in the cities or educated in private schools were more overweight/ obese. In the 2nd phase, an online-based checklist was sent to the parents of overweight/obese children, to query about family, demographic and socioeconomic status. Logistic regression on the data of 440 students who participated in this phase revealed that obesity was more common in males, while overweight was more common in female students (OR 2.5, 95% CI 1.5–3.9). Furthermore, 79% of overweight and 21% of obese students’ parents did not know about their children’s excess body weight, before attending this study (OR 7.2, 95% CI 3.8–13.9). In the 3rd phase, mapping with Bayesian model showed a higher prevalence of obesity in the western and southern counties. Setting public health strategies including massive screening and multidisciplinary interventions (at the individual, family, community, and micro, meso, and macro level of policy-making) to address childhood overweight /obesity, particularly in the high-prevalence areas, is recommended.